PENGARUH PENGGUNAAN BAHASA IBU TERHADAP HASIL BELAJAR SISWA DI SEKOLAH DASAR - Ananda, Rizki; Nurjannah, Annisa; Dalillah, Balqis; Fadillah, Shella (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The profound influence of mother tongue utilization on student learning outcomes in elementary schools has been a subject of limited quantitative inquiry despite its acknowledged sociololinguistic importance. This study aims to quantitatively analyze the extent of this impact. Employing a qualitative descriptive literature review approach, this research meticulously gathered, reviewed, and analyzed diverse scholarly sources, including accredited national journals, conference proceedings, reference books, and educational policy documents. Data collection involved searching online databases such as Google Scholar, Garuda, DOAJ, and SINTA, focusing on articles published between 2019 and 2024 that discuss mother tongue use in elementary education and its link to learning outcomes. Content analysis was performed to classify findings into themes like benefits, challenges, and impact on learning. The results reveal that mother tongue use significantly facilitates understanding of concepts, fosters a comfortable and interactive learning environment, enhances student participation, and boosts self-confidence. While excessive reliance on the mother tongue may hinder Indonesian language proficiency, its balanced integration is crucial for effective learning, particularly in areas where students are not yet fluent in Indonesian. This study advocates for strategic incorporation of mother tongue in teaching to optimize learning outcomes while simultaneously supporting the development of Indonesian language skills